ELT During The Covid-19 Pandemic; Practices and Challenges - Ahmad Syafi'i (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
The purpose of this study is to evaluate the practices and challenges of online learning or so called Learning From Home (LFH) in English Department during the even semester 2019/2020 academic year. The subject of this study are 8 lecturers of English Department at STKIP Al Hikmah. This study employed descriptive qualitative research design. The instrument used is daily online teaching monitoring and evaluation questionnaire. The result of this study is categorized into five aspects namely 1) online learning applications frequently used by the lecturers are WhatsApp, Google Classroom, Schoology, Quizizz, E-mail, Zoom Cloud Meeting, Email, and Youtube 2) online learning activities frequently conducted by the lecturers are uploading materials, discussion forum, conducting quizzes, uploading assigment,, and video conferences, 3) scheduled assignment submission rate, 4) students’ participation rate and 5) challenges and alternative solution proposed by the lecturers during the online learning.